Taṭbīqu Ṭorīqotu al Musyābahah Fīy Ta’allumi al Mufrodāt al ‘Arobiyyah Liṭṭullābi al Indonisiyyin - Bin Agil, Idrus Muchsin; Hasyim Amrullah, Hasyim Amrullah; Miftachul Taubah, Miftachul Taubah (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
Today's Indonesian students are generation Z who are pro-gadgets and familiar with technology, so a unique method is needed to familiarize and accept Arabic mufrada in a familiar way that can be accepted by them. The choice of the musyabahah method, which has not been specifically researched and used in learning Arabic, can be used as an alternative learning method, especially for elementary and secondary students. This paper is a literature review based on several books and scientific articles. There are stages of implementation of this deliberation method is: (1) The teacher mentions sentences that are the same between the two languages in terms of writing and pronunciation, for example: including رَبٌّ (Rabb), مَسْجِدٌ (masjid), كُرْسِي (kursi), الأَعْمَال الصَالِحَة (amalsoleh), عَمَل (beramal), عِلْمٌ (ilmu), كِتَابٌ (kitab), التَفْكِيْر(berfikir), حَامِلٌ (hamil), مَجْلِس (majelis), دِيْوَان (dewan), قَبِيْلَة (kabilah), لَذَّة (lezat), قَمِيْص (gamis), اُسْتُدْيُو (studio), مِنْبَرٌ (mimbar), قِرْطَاس (kertas), أَدَبٌ (adab), صِحَّةٌ (sehat), قَبْرٌ (kuburan), نَصِيْحَة (nasihat), (2) Arranging vocabulary whose letters or meanings are similar between Arabic and Indonesian, (3) Simplify a large number of vocabulary words, (4) The teacher prepares abstract words, (5) The teacher gives listening exercises, (6) The teacher gives an explanation of the changes in the sound of letters.